2005
DOI: 10.1086/429694
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza A Virus Replication by Resveratrol

Abstract: We have previously shown that the life cycles of several viruses are influenced by host-cell redox states. Reports of the antioxidant activities of the plant polyphenol resveratrol (RV) prompted us to investigate its effects on influenza virus replication in vitro and in vivo. We found that RV strongly inhibited the replication of influenza virus in MDCK cells but that this activity was not directly related to glutathione-mediated antioxidant activity. Rather, it involved the blockade of the nuclear-cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
169
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(179 citation statements)
references
References 56 publications
7
169
1
2
Order By: Relevance
“…Thereby, it is conceivable that the inhibitory effect of PGG was mainly caused by the direct interaction of PGG with virus. Numerous studies have demonstrated that plant polyphenols including the tea catechins (-) epigallocatechin gallate (EGCG) and theaflavin digallate [34], resveratrol (RV) [26], a polyphenol rich extract (CYSTUS052) [11], pomegranate polyphenol extract (PPE) [13] , oligonol [12], and Hydroxytyrosol (HT) [38], have potent antiviral activity against influenza virus, that are related to the nature of their interactions with viral particles. Additionally, indirect effects of some polyphenols, such as EGCG and strictinin, on host cells that might interfere with virus-cell membrane fusion have also been suggested [23,32].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it is conceivable that the inhibitory effect of PGG was mainly caused by the direct interaction of PGG with virus. Numerous studies have demonstrated that plant polyphenols including the tea catechins (-) epigallocatechin gallate (EGCG) and theaflavin digallate [34], resveratrol (RV) [26], a polyphenol rich extract (CYSTUS052) [11], pomegranate polyphenol extract (PPE) [13] , oligonol [12], and Hydroxytyrosol (HT) [38], have potent antiviral activity against influenza virus, that are related to the nature of their interactions with viral particles. Additionally, indirect effects of some polyphenols, such as EGCG and strictinin, on host cells that might interfere with virus-cell membrane fusion have also been suggested [23,32].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol inhibited the replication of influenza virus in MDCK cells, as a result of the blockade of the nuclearcytoplasmic translocation of viral ribonucleoproteins and the reduced expression of late viral protein, such as HA and matrix protein [67]. Resveratol also improved survival and decreased pulmonary viral titers in influenza virus-infected mice [67].…”
Section: Resveratrolmentioning
confidence: 99%
“…Resveratrol inhibited the replication of influenza virus in MDCK cells, as a result of the blockade of the nuclearcytoplasmic translocation of viral ribonucleoproteins and the reduced expression of late viral protein, such as HA and matrix protein [67]. Resveratol also improved survival and decreased pulmonary viral titers in influenza virus-infected mice [67]. Since resveratrol inhibited the induction of RANTES production by influenza virus infection in A549 lung epithelial cells [68], it is presumed that resveratorol attenuate the activation of macrophages during influenza virus infection.…”
Section: Resveratrolmentioning
confidence: 99%
“…Antiviral effects of RSV have been investigated in several human and animal viruses including influenza A virus (Palamara et al., 2005), Epstein‐Bar virus (Chen, Qiao et al., 2012), herpes simplex virus (Chen, Qiao et al., 2012), HIV (Clouser et al., 2012), and hepatitis C virus (Nakamura et al., 2010). Results from most of these studies indicate that RSV can prevent inhibiting protein synthesis and thus inhibit virus proliferation (Yang et al., 2015).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%